Gender differences in general knowledge: four Croatian studies - Zarevski, Predrag (Array, 2007)
Gender differences in general knowledge are reported for four studies of school students aged 15 and 18 years in Croatia (total n =4430) and the results compared with those obtained on college students in the United States and in Northern Ireland. The results are generally consistent across the three countries in finding that males had more knowledge of the domains of discovery and exploration, finance, geography, history, politics, science and sport. Females had more knowledge in the domains of cookery and medicine. The results extend knowledge in this area by showing the cross-cultural consistency of gender differences in different domains of knowledge, and in showing that these differences are present in mid-adolescence. It is noted that the domains of which males have more general knowledge are concerned with competition between males in sport, current affairs, history and politics. The domains of which females have more general knowledge are concerned with nuturance, expressed in interest in the domains of medicine and nutrition. These gender differences in interests are interpreted in terms of evolutionary psychology.